Calcium Channel Blockers in Kidney Transplant Recipients: Cyclosporine-Era Kidney-Function Effects and Tacrolimus Pharmacokinetic Implications: A Meta-Analysis - Harnavi Harun; Evelin Veronike; Garri Prima Decroli; Muhammad Ridhwan Fatharanifurqan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Post-transplant hypertension and calcineurin-inhibitor nephrotoxicity threaten cardiovascular and graft outcomes after kidney transplantation. Calcium channel blockers offer haemodynamic benefit and alter calcineurin-inhibitor exposure, but cyclosporine and tacrolimus studies assessed different evidence domains. Objective: To pool the comparative effect of calcium channel blockers on kidney-function outcomes in adult kidney transplant recipients, and to distinguish the cyclosporine-era kidney-function evidence from the tacrolimus-era pharmacokinetic implications. Methods: Comparative randomised trials and cohorts in adult kidney transplant recipients were identified through PubMed, the Cochrane Library, citation pathways, and reference checking. Kidney-function outcomes were directionally harmonised. Compatible standardised mean differences were pooled using a restricted maximum-likelihood random-effects model with Hartung–Knapp inference. Prediction intervals, subgroup analyses, influence diagnostics, sensitivity analyses, and Cochrane RoB 2 assessments were completed. Results: At least 22 reports represented at least 21 independent datasets; seven cyclosporine-treated trials with 639 participants supplied compatible kidney-function data. Calcium channel blockers were favoured (Hedges g 0.38, 95% CI 0.11 to 0.66; I²=45.2%; τ²=0.042), although the 95% prediction interval ranged from −0.19 to 0.96. Leave-one-out estimates ranged from 0.26 to 0.45. DerSimonian–Laird and critical-risk sensitivities yielded g 0.38 and 0.37. A tacrolimus clinical subgroup and primary Egger test were not estimable. Conclusion: Calcium channel blockers were associated with modestly better kidney-function measurements during cyclosporine treatment, but very-low-certainty evidence precluded a uniform benefit claim. Tacrolimus evidence instead concerned CYP3A5-dependent exposure and dose sparing; the two evidence streams remain clinically linked but quantitatively non-equivalent.